2007
DOI: 10.1002/ajmg.a.31798
|View full text |Cite
|
Sign up to set email alerts
|

Partial tandem duplication of GRIA3 in a male with mental retardation

Abstract: The genetic factors underlying mental retardation (MR) are very heterogeneous. Recent studies have identified a number of genes involved in MR, several of which lie on the X-chromosome, but the current understanding of the monogenic causes of MR is far from complete. Investigation of chromosomal rearrangements in patients with MR has proven particularly informative in the search for novel genes. Using array-based comparative genomic hybridization analysis, we identified a small copy number gain at Xq25, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 20 publications
2
24
1
3
Order By: Relevance
“…A partial duplication of the GRIA3 gene, including the promoter region and the exons coding for the proximal region of GRIA3, was detected in a single case with autism. Although slightly different based on its size and the number of duplicated exons, this partial duplication is reminiscent of that recently reported in a patient with MR. 23 At the 8p23 locus, gain and loss of material were found, as well as at the 16p11 and 17q21 loci, as recently described. 22,24,25 This suggests that dosage-sensitive genes, whose expression is finely tuned, are located within these rearranged segments.…”
Section: Disease Specificitysupporting
confidence: 66%
“…A partial duplication of the GRIA3 gene, including the promoter region and the exons coding for the proximal region of GRIA3, was detected in a single case with autism. Although slightly different based on its size and the number of duplicated exons, this partial duplication is reminiscent of that recently reported in a patient with MR. 23 At the 8p23 locus, gain and loss of material were found, as well as at the 16p11 and 17q21 loci, as recently described. 22,24,25 This suggests that dosage-sensitive genes, whose expression is finely tuned, are located within these rearranged segments.…”
Section: Disease Specificitysupporting
confidence: 66%
“…Ionotropic glutamate receptors (iGluRs) are related to learning and memory [33]. In vitro functional studies on GRIA3 missense variants have shown that mutations in functional domains of GRIA3 are associated with kinetic changes in AMPA receptor function leading to significant reduction in iGluR3 channel function which is found to be linked with moderate ID [34,35]. Previously, four missense mutations, one whole gene deletion and three duplications have been reported in GRIA3 [34-38].…”
Section: Discussionmentioning
confidence: 99%
“…For the GRIA gene family, there have been reports of a fusion transcript in GRIA2, a de novo interstitial deletion of chromosome 4q32 that contains the GRIA2 loci, missense mutations in the ligand binding and transmembrane domains of the GluA3 subunit (GRIA3), partial tandem duplication that reduced GRIA3 transcript levels, as well as frameshift in the GRIA3 gene ( Fig. 5; Supplemental Table S3) (Chiyonobu et al, 2007;Wu et al, 2007;Bonnet et al, 2009Bonnet et al, , 2012Poot et al, 2010;Tzschach et al, 2010;Hackmann et al, 2013;Philips et al, 2014). These data suggest that mutations within the GRIA gene family participate in a small subset of patients with intellectual disability; however, few cellular or mechanistic studies of these modifications have been reported.…”
Section: Ampa-selective Glutamate Receptorsmentioning
confidence: 99%